Salicylic acid alleviates Pb toxicity in nicotiana tabacum - Abdul Halim, Nurul Izzah; Phang, Ing Chia (2014)
Lead (Pb) is a persistent and widespread environmental toxicant which becomes one of the major environmental problems nowadays. Phytoremediation is a promising technology to clean up Pb contaminant attributing to the ability of plants to accumulate metal in the above-ground part. However, since Pb is a non-essential element, it excessively increases the production of reactive oxygen species, causing oxidative damage in plants. Investigation on compounds capable of reducing Pb-induce oxidative damage would increase Pb tolerance in plants used for phytoremediation. Recent studies have shown that SA has the ability to reverse the effect of oxidative damage in plants. SA has many physiological roles in plants. It is involved in regulation of plant hormone, growth and development including photosynthesis and respiration. SA was found to reverse cadmium (Cd) toxicity in soybean, reduce Cd accumulation in Oriza sativa and lower lipid peroxidation and concentration of hydrogen peroxide and superoxide radical. It is likely that SA would reduce Pb-induced oxidative stress in N. tabacum. In this study, the effects of SA on morphology, physiological parameters, and Pb uptake in N. tabacum grown under Pb treatment were evaluated. Firstly, N. tabacum was propagated and then subjected to SA and Pb treatment. Morphology of plants was visually observed and physiological parameters including plant height, root length, and leaf length and width were measured. Pb content in N. tabacum treated with and without SA was determined. SA was found to reverse Pb toxicity in N. tabacum.